EFFORTS TO IMPROVE ACTIVENESS AND LEARNING OUTCOMES THROUGH SPIN WHEEL LEARNING MEDIA IN PANCASILA LESSONS FOR GRADE II ELEMENTARY SCHOOL STUDENTS - Syafiqah Rahadatul Aisy; Devina Tri Utary; Keiza Rizkia Audina; Nabila Azahra; Mawardi (STMIK Indonesia Banda Aceh, 2026)
- This research aims to improve the involvement and learning outcomes of elementary school second-grade students in Pancasila subjects through the application of the